PEMBERDAYAAN MASYARAKAT LOKAL DALAM PEMANFAATAN ALGA COKELAT (SARGASSUM sp.) SEBAGAI PEWARNA ALAMI MIE ACEH DI KOTA MEULABOH - Mohamad Gazali; Zuriat Zuriat (Universitas Teuku Umar, 2019)
The seaweed are one of the potency of the marine biodiversity that give value added in pharmacy and cosmetic. The aim of this community empowerment is to increase the understanding and skill regarding the utilization of seaweed from South West Aceh as natural colour of Aceh Noodle. The community empowerment was conducted on July 2019 that located in Jalan Gajah mada Djohan Pahlawan District West Aceh Regency. The stage of activity including taking raw material, try and error in using natural colour from seaweed and socialization and training. The empowerment community that involved the producer partner in order to create a lot of innovations that useful for local community with utilizing the marine resources potency as foodstuff source and medicine.